Pendapatan Komprehensif Lain Perusahaan Sektor Aneka Industri di Indonesia - Muhammad Kurniawan (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2017)
ABSTRACT The purpose of this study was conducted to investigate how the implementation of the presentation of other comprehensive income after the implementation of the International Financial Reporting Standards. Research subjects are various industry sectors. Other comprehensive income components tested are foreign exchange differences, employee benefits, available financial instruments sold, hedges, asset revaluation, associations and venture. The research object is 42 company data of miscellaneous industry sector. The data analysis method used is cross-tabulation and test of Cramer-V difference. The results of the study conclude that the other components of comprehensive income that are presented differently in the research subjects are foreign exchange differences, available financial instruments for sale, hedging, asset revaluation and association. While the other comprehensive component of the presented income is no different is the employee benefits and joint venture. ABSTRAK Pujuan penelitian ini dilakukan untuk menginvestigasi bagaimana implementasi penyajian other comprehensive income setelah penerapan International Financial Reporting Standars. Subyek penelitian adalah sector aneka industry. Komponen penghasilan komprehensif lain yang diuji adalah selisih kurs, imbalan kerja, instrument keuangan yang tersedia dijual, lindung nilai, revaluasi aset, asosiasi, dan ventura. Obyek penelitian adalah 42 data perusahaan perusahaan sector aneka industry. Metode analisis data yang digunakan adalah tabulasi silang dan uji beda Cramer-V. Hasil penelitian menyimpulkan bahwa komponen penghasilan komprehensif lain yang tersaji berbeda pada subyek penelitian adalah selisih kurs, instrument keuangan yang tersedia dijual, hedging, revaluasi aset dan asosiasi. Sedangkan komponen penghasilan komprehensif lain yang tersaji tidak berbeda adalah imbalan kerja dan ventura bersama. JEL Classification: M41, M16, E42